Seizure underreporting in LGI1 and CASPR2 antibody encephalitis. Issue 9 (4th July 2022) - Baumgartner, Tobias; Pitsch, Julika; Olaciregui‐Dague, Karmele; Hoppe, Christian; Racz, Attila; Rüber, Theodor; Becker, Albert; von Wrede, Randi; Surges, Rainer
Abstract: Patients with anti‐leucine‐rich glioma‐inactivated 1 protein (LGI1) or anti‐contactin‐associated protein 2 (CASPR2) antibody encephalitis typically present with frequent epileptic seizures. The seizures generally respond well to immunosuppressive therapy, and the long‐term seizure outcome seems to be favorable. Consequentially, diagnosing acute symptomatic seizures secondary to autoimmune encephalitis instead of autoimmune epilepsy was proposed. However, published data on long‐term seizure outcomes in CASPR2 and LGI1 antibody encephalitis are mostly based on patient reports, and seizure underreporting is a recognized issue. Clinical records from our tertiary epilepsy center were screened retrospectively for patients with LGI1 and CASPR2 antibody encephalitis who reported seizure freedom for at least 3 months and received video‐electroencephalography (EEG) for >24 h at follow‐up visits. Twenty (LGI1, n = 15; CASPR2, n = 5) of 32 patients with LGI1 ( n = 24) and CASPR2 ( n = 8) antibody encephalitis fulfilled these criteria. We recorded focal aware and impaired awareness seizures in four of these patients (20%) with reported seizure‐free intervals ranging from 3 to 27 months. Our results question the favorable seizure outcome in patients with CASPR2 and LGI1 antibody encephalitis and suggest that the proportion of patients who have persistent seizures may be greater. Our findings underline the importance of prolonged video‐EEG telemetry in this population.